Influence of temperature on the release of plasminogen activator. - Fracasso, J. F.; Rodrigues, L. A.; Yashuda, Y. (My University, 1988)
Fibrinolysis is a basic defense mechanism of the organism designed to control the deposition of fibrin in the vascular system and elsewhere. Fibrinolytic activity was measured by the fibrin plate method for three groups of rats (N = 6) that were maintained at room temperature, 20-25 degrees C, 3 degrees C or 38 degrees C for 4 h before testing. Based on measurement of fibrinolytic activity, the level of plasminogen activator released from isolated aortic segments of rats maintained at room temperature (24-28 degrees C) differed significantly from that of the 38 degrees C group. The animals maintained at 3 degrees C did not release plasminogen activator, suggesting that the fibrinolytic response was impaired at low temperature.
Keywords: plasminogen activator; animal; aorta; arteriosclerosis; blood; exercise; fibrinolysis; metabolism; rat; temperature; thrombosis; Animal; Aorta; Arteriosclerosis; Exertion; Fibrinolysis; Plasminogen Activators; Rats; Support, Non-U.S. Gov't; Temperature; Thrombosis